Kajian Strukturalisme Genetik Lucien Goldmann terhadap Representasi Pandangan Dunia Rakyat Kecil dalam Puisi Wiji Thukul" - S. Nani, Sandi; Hadji, Delvina; Hidayanti Ali, Ayu; Umam Kau, Munkizul (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study analyzes the worldview of the lower class in Wiji Thukul's poetry using Lucien Goldmann's genetic structuralism approach. Thukul's poems, born from the socio-political context of the New Order regime, depict the reality of suffering and the struggles of marginalized lower-class communities. Through Goldmann's theory, literary works are understood as manifestations of the collective consciousness of a social class, meaning Thukul's poetry is not merely individual expression but also reflects broader social conflicts. Employing a qualitative method, the research examines how poetic elements mirror the socio-economic conditions of the lower class, including repression, injustice, and the spirit of resistance. The analysis reveals that these poems serve as a medium for articulating resistance against oppressive social structures while fostering collective consciousness for change. Thus, Thukul's works can be interpreted as products of the dialectic between societal structures and the lower class's worldview, reinforcing the concept of homology between literary and social structures in Goldmann's genetic structuralism framework.